Diabetes mellitus management in dental practice - Masudi, Ninin Sukminingrum (Pusat Pengajian Sains Pergigian, Universiti Sains Malaysia, 2011)
Introduction. A number of oral disorders have been associated with diabetes mellitus (DM) such as: periodontal diseases, dental caries, salivary dysfunction, oral mucosal diseases, oral infections such as candidiasis, taste and other neurosensory disorders. Objectives. Advances in under-standing the relationship between oral disease and systemic conditions need to be translated into clinical practice. Dentist should be active in the involvement in-office management of the patient with type 1 or type 2 DM. Patients with long-standing, poorly controlled DM are at risk of developing oral candidiasis, and the evidence indicates that periodontitis is a risk factor for poor glycemic control and the development of other clinical complications of DM. Discussion. DM is a disease of which the general public and practicing dentists should be aware. On the basis of the available data, we can conclude that practicing dentists can have a significant, positive effect on the oral and general health of patients with DM. Since higher population is thought to have DM, a greater role for the oral health care team in the management of the care of patients with DM is both warranted and appropriate. Although many aspects of this new component of dental practice need to be developed, it is an opportunity the dental profession should embrace. Conclusion. Dentists need to be involved in the prevention and management of DM to improve the treatment of oral disease. By actively intervening to identify and monitor patients with DM, dentists have an opportunity to improve patients' oral and systemic health.